Human Blood Identification in Crime Scene as a Forensic Clue (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background:Blood is one of the most common clues found at crime scenes. Human blood is diagnosed according to the following context: first, the location of the blood spots, then virtual tests, then confirmatory tests. Genetic testing and serological testing are important tests in forensic medicine..Materials and Methods:Thirty blood samples were collected in EDTA tubes, of which 25 were collected from humans and five from sheep. This study lasted five months from 23/3 to 22/8/2022. This study was conducted at Babylon University - College of Science - Department of Biology. The aim of this study was to evaluate the Hightop kit for detection of human blood. The blood was exposed to different weather conditions. Then it was examined using this kit to determine the ability of the antigen to withstand different conditions and the sensitivity of the measurement for this kit.Results:The positive results of blood stains that were exposed to different weather conditions for 30 days, except for blood stains that were placed on a smooth surface, showed negative results after 10 days of exposure, as opposed to those that were buried in the soil or blood stains on clothes that endured weather conditions for 30 days..Conclusion:The  Hightop kit is suitable in the field of forensic medicine to determine human blood that is exposed to harsh environmental conditions, as well as the ability to distinguish human blood from animal blood and its target antigen bears the weather conditions.